Pre-attentive cortical processing of behaviorally perceptible spatial changes in older adults—a mismatch negativity study - Freigang, Claudia; Rübsamen, Rudolf; Richter, Nicole (Frontiers in Neuroscience, 2014)
From behavioral studies it is known that auditory spatial resolution of azimuthal space declines over age. To date, it is not clear how age affects the respective sensory auditory processing at the pre-attentive level. Here we tested the hypothesis that pre-attentive processing of behaviorally perceptible spatial changes is preserved in older adults. An EEG-study was performed in older adults (65-82 years of age) and a mismatch negativity (MMN) paradigm employed. Sequences of frequent standard stimuli of defined azimuthal positions were presented together with rarely occurring deviants shifted by 10 degree or 20 degree to the left or to the right of the standard. Standard positions were at +5° (central condition) from the midsagittal plane and at 65° in both lateral hemifields (±65°; lateral condition). The results suggest an effect of laterality on the pre-attentive change processing of spatial deviations in older adults: While for the central conditions deviants close to MAA threshold (i.e. 10 degrees) yielded discernable MMNs, for lateral positions the respective MMN responses were only elicited by spatial deviations of 20 degrees towards the midline (i.e. ±45°). Furthermore, MMN amplitudes were found to be insensitive to the magnitude of deviation (10 degree, 20 degree), which is contrary to recent studies with young adults (Bennemann et al., 2013) and hints to a deteriorated pre-attentive encoding of sound sources in older adults. The discrepancy between behavioral MAA data and present results are discussed with respect to the possibility that under the condition of active stimulus processing older adults might benefit from recruiting additional attentional top-down processes to detect small magnitudes of spatial deviations even within the lateral acoustic field.